Ultrasonic assisted micro-shear punching of amorphous alloy. Issue 10 (3rd October 2018) - Luo, Feng; Sun, Fei; Li, Kangsen; Gong, Feng; Liang, Xiong; Wu, Xiaoyu; Ma, Jiang
ABSTRACT: Despite the excellent properties, amorphous alloys find limited applications and to find plastic forming ability has been a longstanding problem. In this work, an effective ultrasonic assisted micro-shear punching (UMSP) method is proposed for amorphous alloys. By applying ultrasonic vibration and molten plastics viscous medium, a series of shapes and products with micro-length scale to macro-length scale can be successfully fabricated in 50 ms. Different from traditional crystalline alloys, the amorphous alloys become soft at certain regions during the ultrasonic hammering owing to the unique disordered structures, thereby resulting in the low-stress forming approach. GRAPHICAL ABSTRACT: IMPACT STATEMENT: In this work, a new acting mechanism was found between amorphous alloy and the high-frequency vibration, providing an efficient approach for the fabrication of amorphous alloy products.